Tax System Problems as a Cause of Sustainable Poverty in Japan: an Analysis of the Tax System in an Islamic View - Latief, Mohamad; Rimapradesi, Yulia; Cahyani, Mustika; Nurcahyani, Ratna Alfina (Universitas Islam Lamongan, 2024)
Japan is one of the developed countries in East Asia. It can be seen from advances in technology, education and a high level of discipline. However, poverty has hit this country due to problems with the tax system and the increase in elderly people. The research methodology used in this research is a descriptive qualitative research method. This article aims to provide a solution to the problem of poverty that occurs in Japan through the implementation of a zakat system based on the Koran and Sunnah. The urgency of this research is to offer or propose a solution to the problem of poverty for the Japanese embassy. The results of this research show that persistent poverty in Japan can be eradicated by implementing a taxation system based on the concept of zakat nishab, so that tax payments do not burden those who pay zakat and there is no excess payment to avoid embezzlement of funds by greedy individuals.